Impact of stress,immunity,and signals from endocrine and nervous system on fascia - Barsotti, N.; Chiera, M.; Lanaro, D.; Fioranelli, M. (EWF Scientific Magazine, 2020)
The hypothalamic-pituitary-adrenal (HPA) axis and the stress response are paramount for the organism to cope with physical threats or psychosocial adversities. Extensive knowledge has been gained on how: 1.the stress response can affect every endocrine axis; 2.many cells of several tissues can produce and secrete stress hormones (and also catecholamines) that can impact the cen-tral HPA axis and the whole body; 3.the HPA axis can heavily influence the immune system; 4.the stress response can affect the body structure. Fascia is a particular kind of connective tissue - different from blood, cartilage, and bones - having a ubiq-uitous, multi-functional nature: itprovides the structural and function-al architecture of the body. The fascia integrates the functions of several systems (e.g., the nervous, immune, and cardiovascular systems) and can transmit mechanical, chemical, and electrical information. The fascia has no universal-ly accepted definition of it, butsince defining fascia is not our pur-pose, we refer the reader to the appropriate references. For the sake of simplicity, we will consider the terms "fascia" and "fascialsystem" according to the definition given by Carla Stecco and RobertSchleip in an editorial about fascia science and its clinical applications: a fascia is "a sheath, a sheet or any number of other dissectible aggregations of connective tissue that forms beneath the skin to attach, enclose, separate muscles and other internal organs," whereas the fascial system is "a network of interacting, interrelated, interdependent (fascial) tissues forming a complexwhole, all collaborating to perform amovement." This definition of "fascia" can be use-ful to describe anatomical features, whereas the term "fascial system"may prove helpful to manual thera-pists in explaining what occurs during a manual therapy session.